Does Modern Consumerism Bring Sustainability in Responsible Consumer Behavior? The Case of Household Waste in Indonesia - Ardhiyansyah, Andri; Ashidiqy, Abu Bakar; Jaman, Ujang Badru (Jurnal Dinamika Manajemen, 2024)
Urbanization, globalization, and economic growth in Indonesia have changed consumer behaviors, leading to more household waste and environmental damage. Modern consumerism, fueled by a neoliberal economic model, worsens these issues as Indonesia’s waste management systems fail to keep up with the increasing waste from growing urban and middle-class populations. This study examines how knowledge, personalization, and word-of-mouth marketing, three components of contemporary consumerism, affect sustainable and ethical consumer behavior, particularly with regard to home trash management in Indonesia. A quantitative technique was used, and 370 Indonesian homes were surveyed. A structured questionnaire with a Likert scale (1–5) was used to gather the data, and (SEM-PLS 3) was used for analysis. The findings demonstrated that word-of-mouth, personalization, and informativeness had a major influence on the intention to decrease waste as well as the formation of waste reduction behaviors. In turn, these behaviors and intentions strongly indicate long-term, responsible behavior. These findings underscore the crucial role of modern consumerism’s components in shaping responsible waste management practices. As the urban and middle-class demographics continue to grow, the implications for Indonesia’s waste management systems are profound, suggesting a critical need for targeted interventions that leverage personalization and social influence to promote sustainability.